The Internet for Physicians - Smith, Roger P. (Springer New York, 2002)
Like the Internet itself, interest in computing (both local and distant) has grown exponentially. The rapidly changing role of the Internet has resulted in three very different editions of The Internet for Physicians. The first edition attempted to introduce the concept of information transfer and communication and point the way toward a tool of the future. The second edition attempted to assuage trepidation in the use of this emerging tool and suggest the why and wherefore of being connected. The needs that drove those goals have almost completely disappeared. As a result, the bulk of this edition is more focused on the medical aspect of the Internet and its use, and less on the nuts and bolts of connecting and communication through the Web. It has been revamped, reorganized, and expanded to include 30% more content and 90 new illustrations. New to the third edition is an entire section dedicated to Medicine and the Web, with chapters discussing patient education and information, what your patients are seeing on the web, finding quality resources, including clinical-trial and evidence-based medicine sites, how to search and use Pun Med, telemedicine, continuing medical education, medical literature and informatics, applications of on-line journals and submissions, and much more.